Modeling the Dynamics of Cardiovascular Disease Using a SEICRD Framework - Arista Fitri Diana; Mia Siti Khumaeroh; Tarita Intan Soraya (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
Cardiovascular disease remains a major public health challenge worldwide, often progressing silently toward chronic complications. Increasing awareness through media and individual behavioral responses plays an important role in preventing disease transmission and reducing long-term complications. Motivated by this, we formulate a deterministic compartmental model to investigate the dynamics of cardiovascular disease by incorporating media awareness and individual awareness as control-related parameters. The population is divided into susceptible, exposed, infected, chronic, recovered, and deceased compartments. A qualitative analysis of the linear dynamical system is carried out, including positivity of solutions, bound- edness, equilibrium points, and local stability analysis using eigenvalue criteria. Numerical simulations are performed to illustrate the effects of key epidemiological and awareness-related parameters on disease progression. The simulation results indicate that increased media and individual awareness significantly reduce the long-term burden of chronic cardiovascular complications. In contrast, higher incidence and disease progression rates lead to increased accumulation in the chronic compartment, even when the number of active infections declines more rapidly. Sensitivity analysis confirms that awareness parameters have a negative influ- ence on chronic disease prevalence, whereas core epidemiological parameters exert a strong positive effect. These findings highlight the critical role of awareness-based interventions in mitigating chronic cardiovascular disease and provide a quantitative framework to support effective prevention and control strategies.